The Simulation Of Return Period Design Flood At KG2 Setail Storage Planning In Yosomulyo Village Gambiran Sub District Banyuwangi - Yuda Pratama Gumelar; Zulis Erwanto; Andi Wijanarko (Indonesian Society of Applied Science, 2020)
Based on Banyuwangi Regency Regulation Number 08 of 2012 concerning the Spatial Planning of the Banyuwangi Regency in 2012 related to the development of reservoirs and storages. To meet the irrigation water needs in Yosomulyo Village, the construction of the KG2 Setail storage is required. The purpose of this study was to determine the results of the flood discharge simulation of the KG2 Setail storage planning using the HEC-RAS program. For the calculation of flood discharge when using the rational method. For flood design simulations using the assist of the HEC-RAS (Hydrology Engineering Center - River Analysis System) program by inserting a cross-section of the storage. From the results of a flood simulation with the HEC-RAS assistance program in the KG2 Setail storage planning with a 1-year return planning discharge of 41.21 m3/sec, a 2 year return period of 90.30 m3/sec, a 5 year return period of 112.78 m3/sec, when the 10-year return period was 125, 16 m3/sec, the 20-year return period was 136.29 m3/sec and the 25-year return period was 138.63 m3/sec, there was no overflow of water in the design according to plan The KG2 Setail storage can be set aside to allocate a discharge of up to 25 years by the original plan with a storage capacity of 384.37 x 103 m3.